PENGEMBANGAN MEDIA PEMBELAJARAN BERUPA GAME EDUTAINMENT UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA - Herlina Herlina; Nurmala R (Mathematics Education And Application Journal (META), 2019)
AbstractThis research is a development research that aims to produce instructional media to know the qualityof game edutainment to improve the mathematics learning motivation ofstudent’s class IX SMPN 5 Tarakan based on expert validation and field testing. The development of this instructional media used the development model adopted from Thiagarajaran’s 4D  which consists of 4 stages include the define, design, development and disseminate. The result of the analysis showed that the game edutainment developed was based validation from three validators after averaging was obtained valid criteria with 76,83% which it is valid to be used. The result of the analysis from student in field testing was obtained very practical criteria with 83,31%. Then, the result of the analysis of student motivation in the field testing was obtained  effective criteria with 78,57%  so that the developed media can be said of quality to improve the mathematics learning motivation of student’s class IX SMPN 5 Tarakan. Keywords: Development, Media, Game EdutainmentAbstrakPenelitian ini merupakan penelitian pengembangan yang bertujuan untuk menghasilkan media pembelajaran berupa game edutainment yang berkualitas untuk meningkatkan motivasi belajar matematika siswa kelas IX SMPN 5 Tarakan berdasarkan hasil validasi ahli dan uji lapangan. Pengembangan ini menggunakan model pengembangan yang diadaptasi dari model Thiagarajan yaitu 4D yang terdiri atas 4 tahap yang meliputi tahap define, design, development dan disseminate. Hasil analisis menunjukkan bahwa game edutainment yang dikembangkan berdasarkan hasil validasi dari ketiga validator setelah dirata-ratakan diperoleh persentase kevalidan media sebesar 76,83% dengan kriteria valid. Berdasarkan hasil analisis respon siswa pada uji lapangan diperoleh persentase 85,31% dengan kriteria sangat praktis. Kemudian hasil analisis motivasi siswa pada uji lapangan diperoleh persentase 78,57% dengan kriteria efektif sehingga media yang dikembangkan dapat dikatakan berkualitas untuk meningkatkan motivasi belajar siswa kelas IX SMPN 5 Tarakan.Kata Kunci: Pengembangan,Media, GameEdutainment